The Potent Trypanocidal Effect of LQB303, a Novel Redox-Active Phenyl-Tert-Butyl-Nitrone Derivate That Causes Mitochondrial Collapse in Trypanosoma cruzi - Macedo, Carolina Machado; Saraiva, Francis Monique de Souza; Paula, Jéssica Isis Oliveira; Nascimento, Suelen de Brito; Costa, Débora de Souza dos Santos; Costa, Paulo Roberto Ribeiro; Dias, Ayres Guimarães; Paes, Marcia Cristina; Nogueira, Natália Pereira (Frontiers in Microbiology, 2021)
Chagas disease, which is caused by Trypanosoma cruzi, establishes lifelong infections in humans and other mammals that lead to severe cardiac and gastrointestinal complications despite the competent immune response of the hosts. Furthermore, it is a neglected disease that affects 8 million people worldwide. The scenario is even more frustrating since the main chemotherapy is based on benznidazole, a drug that presents severe side effects and low efficacy in the chronic phase of the disease. Thus, the search for new therapeutic alternatives is urgent. In the present study, we investigated the activity of a novel phenyl-tert-butyl-nitrone (PBN) derivate, LQB303, against T. cruzi. LQB303 presented trypanocidal effect against intracellular [IC50/48h= 2.6 µM] and extracellular amastigotes [IC50/24h= 3.3 µM] in vitro, leading to parasite lysis; however, it does not present any toxicity to host cells. Despite emerging evidence that mitochondrial metabolism is essential for amastigotes to grow inside mammalian cells, the mechanism of redox-active molecules that aim T. cruzi mitochondrion is still poorly explored. Therefore, we investigated if LQB303 trypanocidal activity was related to the impairment of the mitochondrial function of amastigotes. The investigation showed there was a significant decrease compared to the baseline oxygen consumption rate (OCR) of LQB303-treated extracellular amastigotes of T. cruzi, as well as reduction of “proton leak” (depletion of the proton motive force by inhibition of F1Fo ATP synthase) and "ETS" (maximal oxygen consumption after uncoupling) oxygen consumption rates. Interestingly, the residual respiration ("ROX") enhanced about three times in LQB303-treated amastigotes. The spare respiratory capacity ratio (SRC: cell ability to meet new energy demands) and the ATP-linked OCR were also impaired by LQB303 treatment, correlating the trypanocidal activity of LQB303 with the impairment of mitochondrial redox metabolism of amastigotes. Flow cytometric analysis demonstrated a significant reduction of the ΔΨM of treated amastigotes. LQB303 had no significant influence on the OCR of treated mammalian cells, evidencing its specificity against T. cruzi mitochondrial metabolism. Our results suggest a promising trypanocidal activity of LQB303, associated with parasite bioenergetic inefficiency, with no influence on the host energy metabolism, a fact that may point to an attractive alternative therapy for Chagas disease.Potential